Peran Youtuber dengan Penonton dalam Menjalankan Gaya Hidup Sehat New Normal (Studi Kasus Youtuber Shiely Venessa) - Jesvanny Jesvanny; Riris Loisa; Sisca Aulia (Koneksi, 2022)
The development in the 4.0 industrial revolution resulted in the internet developing rapidly, so that the application of technology has spread throughout all sectors. This was coupled with the Covid-19 pandemic, and made changes in the pattern of people's lives in Indonesia which led to an increase in internet users in Indonesia to 175.4 million million or it can be said that 50 % of the total population of Indonesia. And the social media that is in the spotlight is Youtube so it is used in this study. The purpose of this study is to determine whether there is a role for Youtuber and the audience in carrying out a new normal healthy lifestyle. The research method used in this research is qualitative with data collection techniques in the form of observation and interviews with YouTubers and Subscribers, and with the aim of knowing whether there is a Youtuber role with the audience in carrying out a new normal healthy lifestyle. The results of the study show that YouTubers are very interested in creating content about this new normal healthy lifestyle and Subscribers and Viewers provide good comments and responses with new normal healthy lifestyle content.Perkembangan dalam revolusi industri 4.0 mengakibatkan internet berkembang dengan pesat, hingga penerapan teknologi pun telah menyebar di seluruh sektor. Hal ini ditambah dengan pandemi Covid-19 yang membuat perubahan dalam pola hidup masyarakat Indonesia. Pengguna internet di Indonesia melonjak hingga 175,4 juta jiwa atau dapat dikatakan 50% dari total penduduk Indonesia. Penggunaan media sosial juga melonjak salah satunya Youtube. Penelitian ini ingin mengetahui ada tidaknya peran youtuber dengan penonton dalam menjalankan gaya hidup sehat new normal. Metode penelitian yang digunakan dalam penelitian ini adalah kualitatif dengan teknik pengumpulan data berupa observasi dan wawancara dengan youtuber dan pelanggan (subscriber), dan dengan tujuan untuk mengetahui ada tidaknya peran youtuber dengan penonton dalam menjalankan gaya hidup sehat new normal. Hasil dari penelitian menunjukan bahwa para youtuber sangat tertarik untuk membuat konten tentang gaya hidup sehat new normal, subscriber dan penonton (viewer) memberikan komentar dan tanggapan yang baik dengan konten gaya hidup sehat new normal.